PERANAN GURU BIMBINGAN KONSELING TERHADAP PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Imam Syafi'i; Ika Qurrotul Afifah (JEA (Jurnal Edukasi AUD), 2021)
The writing of this article contains an overview of the important role played by guidance and counseling teachers during covid-19. With the aim of finding a bright spot on the problems experienced by students during online learning. Given that some activities outside the home are limited, researchers have the opportunity to use the literature study method. Techniques for collecting data are sufficient by reviewing book references, journal articles and social media if necessary. From the data that has been collected, the next step is to analyze it so that conclusions can be easily drawn. Building communication and friendship between teachers and parents allows a counseling guidance teacher to have an idea of how to create an online learning atmosphere that is not boring. So that students will be enthusiastic and enthusiastic in participating in these activities.Keywords: teacher role, guidance and counseling, online learning